Investigation on the Efficacy of a Killed Salmonella pullorum Vaccine - Akter, Mst Shamima; Saha, Sukumar; Islam, Md Ariful; Hossain, Md Golzar (Microbes and Health, 2013)
This study was carried out to determine the efficacy of a formalin-killed alum-precipitated Salmonella pullorum vaccine prepared by the Livestock and Poultry Vaccine Research and Production Centre (LPVRPC), BAU, Mymensingh, Bangladesh. Immunization with this vaccine induced serum antibody titers that peaked in 2-week following both primary and booster vaccination (P<0.05), and started to decline following 4-week of both vaccinations. Both primary and booster vaccination induced detectable antibody responses that were able to react with whole cells S. pullorum as determined by passive haemagglutination test (PHA). Both vaccinated chicken and mice showed maximal resistance following challenge with a virulent isolate of S. pullorum (P<0.01). In differential leukocyte counts in mice, a significant increase of lymphocytes was observed after primary immunization (P<0.01). Sera from vaccinated chickens conferred superior protection over naive chickens from lethal challenge with S. pullorum (P<0.01). Finally, this result indicates that S. pullorum vaccine is effective for controlling pullorum disease and antibody is crucial for protection. DOI: http://dx.doi.org/10.3329/mh.v1i1.13707 Microbes and Health Vol.1(1) June 2012 pp.14-18